Fotoluminescência de nanopartículas de Ni(OH)2 e avaliação catalítica de NiO na redução de NO com CO - Moura, Ana Paula de (Universidade Federal de São Carlos, 2010)
In recent years, nanostructured oxides have attracted great interest from different areas of technology due to the possibility of developing new devices or electro-optical equipment. In principle, the physical and chemical properties of these compounds are governed by the distribution, shape and size of their particles. Currently, conventional hydrothermal methods have enabled the training of various oxides with different morphologies and degree of crystallinity, with the use of low temperature synthesis or processing (> 200 oC). Moreover, the main disadvantage of these systems lies in their long treatment times, which was circumvented by the use of microwave radiation as the heating source. This new equipment has become known as microwave hydrothermal (MH). So in this work, nickel hydroxide (Ni (OH) 2) was synthesized by hydrothermal microwave in the presence of cetyl trimethyl ammonium (CTAB) and polyethylene glycol (PEG). Also, these summaries were analyzed the influence of different chemical bases (ammonium hydroxide (NH4OH) and sodium hydroxide (NaOH)) and the effect of hydrothermal treatment times. The nickel oxide was obtained through the thermal decomposition of precursor (Ni(OH)2) previously formed. For this we used thermal treatment temperature of 300 oC and 500 oC in a microwave oven for a period of 2 min. These samples were investigated by X-ray diffraction (XRD), infrared analysis (FTIR) spectroscopy, micro-Raman (MR) scanning electron microscope by field emission gun high resolution (FEG-SEM), electron microscopy transmission (TEM) and reduction with hydrogen temperature programmed (TPR-H2). The optical properties were studied by ultraviolet-visible spectroscopy (UV-vis) and photoluminescence measurements. The X-ray diffraction showed that both Ni(OH)2 and NiO have a high degree of crystallinity and are structurally ordered at long range. The FTIR spectra and MR exhibited characteristic bands for these materials. The microscopy images of FEG-MEV and TEM indicate the formation of plaques with irregular shapes, nature and agglomerated nanometric dimensions. The UV-vis spectra suggested the existence of intermediate energy levels within the band gap. When excited with a Tese de doutorado Ana Paula de Moura VI wavelength of 350 nm, Ni(OH)2 showed a broadband emission photoluminescence in the blue and also red in the visible spectrum. RTP-H2 curves for NiO showed the presence of peaks on the reduction of Ni2 + to nickel metal. The samples showed catalytic properties of NiO on the reaction of CO / NO.
Keywords: Físico-química; Microondas; Níquel; Nanopartículas; Catalisadores; Fotoluminescência; CIENCIAS EXATAS E DA TERRA::QUIMICA